Hydro-geochemical assessment to evaluate the suitability of groundwater for domestic and irrigation purpose in parts of Sindhudurg District, Maharashtra - Erram, Vinit C.; Gupta, Gautam; Laxminarayana, M.; Naidu, Suneetha; Shailaja, G. (My University, 2016)
Groundwater is regarded as one of the major sources of drinking water for the society. It is also used for agricultural, industrial, and various other domestic purposes. However, intrusion of saline water, particularly in the coastal areas, creates a major concern for its safe uses. In addition to this, the coastal aquifers are subjected to various harmful contaminants, such as agricultural fertilizer, pesticides and waste. The main objectives of the present study are to assess and classify the groundwater quality for domestic and irrigation purpose of western Maharashtra. A total of 85 vertical electrical sounding points have been acquired from the study area. Also water samples have been taken from 36 locations. The true resistivity contour map shows moderate resistivity in the central part of the study area at a depth of 10 in and 15 m. The north—eastern part of the area shows higher resistivity values at 10 in to 20 in due to the presence of hard rock beneath; whereas south—western part reveals the lowest resistivity values from 1 in to 15 in of depth indicating the presence of saline water. The groundwater quality of the study area is classified into three categories: “Very good”, “Good”, and “Unsuitable”. Water quality index of the study area shows that more than 50% of groundwater is in the range of excellent to good quality, while parameters analysed for the irrigation suitability of water are found to be in good to moderate in most cases except at a few places within the study area.
Keywords: Groundwater Quality; Maharastra; Resistivity; Coastal acquifer; Sindhudurg